CPP-calcification of articular cartilage is associated with elevated cytokine levels in synovial fluid - Stücker, Sina; Koßlowksi, Franziska; Buchholz, Adrian; Schwab, Andrea; Halm-Pozniak, Agnieszka; Lohmann, Christoph H.; Bertrand, Jessica (Frontiers in Cell and Developmental Biology, 2025)
BackgroundCalcification of articular tissues is commonly observed in later osteoarthritis (OA) stages and can be caused by basic calcium phosphate (BCP) or calcium pyrophosphate (CPP) crystals. Calcification, particularly CPP deposition, has recently been associated with inflammation and cellular senescence. Investigating this association, we analyzed the concentration of various inflammatory mediators in synovial fluid and synovial membrane of OA patients in relation to calcification and the different crystal types.MethodsSynovial fluid was collected from OA patients during joint replacement surgery. Cytokine concentrations were measured using magnetic bead-based multiplex assay using Luminex® technology. Radiographs were used to determine and grade calcification of the knee joint and involved calcium crystal types were identified via Raman spectroscopy.ResultsSynovial fluid of patients with radiological calcification showed elevated levels of multiple cytokines (IL-10, IL-15, IL-1ra, GM-CSF), chemokines (IL-8, MCP-1, MIP-1b) and growth factors (PDGF-AB/BB, VEGF). Crystal differentiation revealed higher synovial fluid concentrations of IL-15, IL-1ra, IL-10, GM-CSF, PDGF-AB/BB and MIP-1b in patients with CPP- compared to BCP-calcified cartilage.ConclusionWe show an elevated cytokine profile in synovial fluid of patients with radiological calcification that may be linked to CPP depositison in cartilage.